A novel knockout mouse model of the noncoding antisense Brain-Derived Neurotrophic Factor (Bdnf) gene displays increased endogenous Bdnf protein and improved memory function following exercise - Modarresi, Farzaneh (Heliyon, 2021)
Brain-derived neurotrophic factor (Bdnf) expression is tightly controlled at the transcriptional and post-transcriptional levels. Previously, we showed that inhibition of noncoding Bdnf antisense (Bdnf-AS) RNA upregulates Bdnf protein. Here, we generated a Bdnf-antisense knockout (Bdnf-AS KO) mouse model by deleting 6 kilobases upstream of Bdnf-AS. After verifying suppression of Bdnf-AS, baseline behavioral tests indicated no significant difference in knockout and wild type mice, except for enhanced cognitive function in the knockout mice in the Y-maze. Following acute involuntary exercise, Bdnf-AS KO mice were re-assessed and a significant increase in Bdnf mRNA and protein were observed. Following long-term involuntary exercise, we observed a significant increase in nonspatial and spatial memory in novel object recognition and Barnes maze tests in young and aged Bdnf-AS KO mice. Our data provides evidence for the beneficial effects of endogenous Bdnf upregulation and the synergistic effect of Bdnf-AS knockout on exercise and memory retention.